Quality of life, anxiety, and depression improve at one-year after liver transplantation in patients with advanced liver disease - Cordoba-Alvarado, Rosana; Romero-Fonnegra, Valentina; Cortes-Mejia, Nicolas; Bejarano-Ramirez, Diana Fernanda; Maldonado-Hoyos, Valentina; Sanchez-Garcia, Sandra Janeth; Vera-Torres, Alonso (Frontiers in Transplantation, 2024)
BackgroundLiver transplantation (LT) improves survival in end-stage liver disease. Several reports have addressed the impact of LT on patients’ lives, beyond purely medical outcomes. Although the quality of life and mental health have been demonstrated to improve with this procedure, such studies are still missing in Latin America.MethodsPatients who received LT at the Fundación Santa Fe de Bogotá between 2017 and 2019 were assessed for quality of life (QoL), anxiety, and depression and they were followed up for one year after the procedure. Pre-transplant data were gathered at inclusion on the waiting list, while post-transplant data at 3- and 12 months after LT. European Quality of Life-5 Dimensions (EQ-5D) and European Quality of Life-Visual Analog Scale (EQ-VAS) instruments were used to evaluate QoL. The Hospital Anxiety and Depression Scale (HADS) was used for evaluating anxious and depressive symptoms.Results115 recipients met the inclusion criteria. Mean pre-transplant EQ-VAS was 70.78, rising to 87.16 and 92.56 at 3- and 12-months, respectively. Improvements in all EQ-5D dimensions were found in response to LT. According to the HADS questionnaire, anxiety was reduced by 2.35 points and depression by 1.63 points after LT.Conclusionin the short term, LT is a successful strategy for enhancing QoL, anxiety, and depression in patients with liver disease. Long-term benefits must be assessed.